2013
DOI: 10.1007/s12013-013-9679-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Dicer, miRNAs, and Inflammatory Markers in Diabetic Ins2+/− Akita Hearts

Abstract: Diabetic cardiomyopathy is a leading cause of morbidity and mortality, and Insulin2 mutant (Ins2+/−) Akita is a genetic mice model of diabetes relevant to humans. Dicer, miRNAs and inflammatory cytokines are associated with heart failure. However, the differential expression of miRNAs, dicer and inflammatory molecules are not clear in diabetic cardiomyopathy of Akita. We measured the levels of miRNAs, dicer, pro-inflammatory tumor necrosis factor alpha (TNFα), and anti-inflammatory interleukin 10 (IL-10) in C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 78 publications
9
83
2
1
Order By: Relevance
“…HHcy inactivates and down regulates MEF2C in the cardiomyocytes (Figure 3A–C). Since miR-133a is attenuated in the failing human hearts [24] and in diabetic hearts [22, 28], and its role is established as anti-hypertrophy [24, 39] and anti-fibrosis [22, 23], our results suggest a new role of Hcy in miR-133a mediated pathological remodeling in the heart, which is relevant to the human heart failure.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…HHcy inactivates and down regulates MEF2C in the cardiomyocytes (Figure 3A–C). Since miR-133a is attenuated in the failing human hearts [24] and in diabetic hearts [22, 28], and its role is established as anti-hypertrophy [24, 39] and anti-fibrosis [22, 23], our results suggest a new role of Hcy in miR-133a mediated pathological remodeling in the heart, which is relevant to the human heart failure.…”
Section: Discussionmentioning
confidence: 88%
“…The miRNA Reverse Transcriptase-PCR followed by Taqman qPCR were performed using miR-133a (Assay ID-002246) and U6 SnRNA (Assay ID: 001973) specific primers following the manufacturer’s instruction and protocol (Life technologies, USA). The details of the protocol is published elsewhere [28]. U6 SnRNA was used as an endogenous control for miR-133a.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that miR-133a has a role in the contractility of the pressure-overload heart (27) and that miR-133a is downregulated in diabetic hearts (28). To determine whether the lack of miR-133a decreased the contractility of the diabetic heart, we overexpressed miR-133a in the diabetic hearts by miR-133a mimic treatment and validated the upregulated miR-133a in the diabetic hearts by individual miR-133a assay (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…↑ Increased (Nielsen et al 2002, Ueno et al 2008, Pulinilkunnil et al 2013, Kuramoto et al 2014, Yan et al 2015, Novgorodov et al 2016 ↑ Increased (Bugger et al 2008, Basu et al 2009, Pulinilkunnil et al 2013 Glucose oxidation ↓ Decreased (Pulinilkunnil et al 2013) ↓ Decreased (Bugger et al 2008, Basu et al 2009) Fatty acid oxidation ↑ Increased (Pulinilkunnil et al 2013) ↑ Increased (Bugger et al 2008, Basu et al 2009) Pathways modulated Inflammation ↑ Increased (Westermann et al 2009) ↑ Increased (Wang et al 2013) ↑ Increased (Chavali et al 2014) Mitochondrial function Dysfunction/abnormal (Pulinilkunnil et al 2013, Xu et al 2013, Novgorodov et al 2016 Dysfunction/abnormal (Shen et al 2004, Ye et al 2004, Xie et al 2011, Vadvalkar et al 2013, Xu et al 2013 Dysfunction/abnormal (Bugger et al 2008(Bugger et al , 2009 (Continued) R233 Review r h ritchie and others Lipid metabolism and diabetic cardiomyopathy impaired folding of proinsulin leading to endoplasmic reticulum (ER) stress in pancreatic islets such that Akita mice exhibit progressive loss of beta-cells, which correlates with diabetes development. Hyperglycaemia is evident from 3 to 4 weeks of age.…”
Section: ) Cardiac Lipidsmentioning
confidence: 99%